Aminoglycoside antibiotics moderately impair granulocyte function. - Seklecki, M M (1978)
By in vitro methods, five aminoglycoside antibiotics (amikacin, kanamycin, gentamicin, tobramycin, and netilmicin) were shown to produce modest changes in granulocyte adherence (increase) and migration (decrease) and no change in phagocytosis or nitroblue tetrazolium reduction.